2012
DOI: 10.1021/es203446w
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of Polychlorinated Biphenyls Volatilizing from the Hudson River, New York Measured Using Micrometeorological Approaches

Abstract: This study represents the first time that a micrometeorological technique, using turbulent transport measurements, has been used to determine the direction and magnitude of air-water exchange of polychlorinated biphenyls (PCBs). The study was conducted during July 2008 on the Hudson River estuary near the Tappan Zee Bridge, which is the site of some of the most serious PCB contamination in the world. Gas-phase ΣPCB concentrations measured at two heights above the water column averaged 1.1 ng m(-3), and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…In addition, Kouznetsova et al (2007) reported elevations in rates of hospitalization for diabetes among individuals living near hazardous waste sites containing PCBs, and suggested that the likely route of exposure was inhalation of vapor-phase PCBs. Living near a PCB-contaminated hazardous waste site would not be expected to increase exposure via ingestion or dermal uptake, but can result in continuous inhalation of vapor-phase PCBs, although this inhalation would vary with season and temperature (Sandy et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kouznetsova et al (2007) reported elevations in rates of hospitalization for diabetes among individuals living near hazardous waste sites containing PCBs, and suggested that the likely route of exposure was inhalation of vapor-phase PCBs. Living near a PCB-contaminated hazardous waste site would not be expected to increase exposure via ingestion or dermal uptake, but can result in continuous inhalation of vapor-phase PCBs, although this inhalation would vary with season and temperature (Sandy et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The values of K pe-a or K pe-w were acquired from previous studies (Bao et al, 2012;Khairy et al, 2014;Reitsma et al, 2013) and corrected for temperature by the van't Hoff equation and for salinity by the Setschenow constant (Schwarzenbach et al, 2003). The Setschenow constant (K Si ; L mol À1 ) used was 0.3 for PAHs (Schwarzenbach et al, 2003) and 0.35 for DDTs (Lohmann, 2012). M pe is the mass of PE (kg).…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, almost all measurements of fugacity gradients of HOCs were conducted with grab sampling methods and passive samplers, i.e., those collected at single points away from the air-water interface in both the atmosphere and within the water column (Guitart et al, 2010;Khairy et al, 2014;Manodori et al, 2007;Mulder et al, 2014). In addition, inter-compartmental fluxes were measured with micrometeorological methods at two different points in the atmosphere (Sandy et al, 2012;Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor air concentrations of PCBs near New Bedford Harbor, a highly contaminated body of water, ranged from 0.4 to 53 ng/m 3 (8); these are significantly higher than those at a comparison site. PCB fluxes to air along the contaminated Hudson River ranged from 0.5 to 13 μg/m 2 /day (9). The greater water solubility of lower chlorinated PCBs has implications for drinking water quality.…”
Section: Introductionmentioning
confidence: 99%